Dawn and Evolution of Cardiac Procedures Research Avenues in Cardiac Surgery and Interventional Cardiology - Picich,̈ Marco. (Springer Milan : Imprint: Springer, 2013)
The origins of cardiac surgery are dramatic. It has evolved through the efforts of visionaries who were often criticized and at times dismissed as mad, as well as the great number of desperate patients who accepted to subject themselves to new and untried procedures in the hope of cheating death. While often disregarded, the history of scientific inquiry has much to teach us, and that of cardiac surgery and interventional cardiology is no exception. To discuss the dawn and evolution of cardiac procedures, an international team of cardiac surgeons, interventional cardiologists, anesthesiologists, perfusionists, and biomedical engineers from 22 centers and six countries have been brought together. Each chapter of this book offers a detailed overview of previous investigative efforts and an understanding of the thinking and mentality behind them. Nevertheless, chapters on the recent history of mini-invasive and sutureless valve surgery have also been included, to further assist the reader in transitioning from past to present and on into the future. The attention devoted to research aspects, the comprehensiveness of the historical overview, and the pedagogic and anecdotal nature of the contents make this text unique in the cardiac field and of utmost interest to researchers, cardiac surgeons, cardiologists, residents, medical historians, and biomedical engineers.